Simplified methodology for large scale isolation of homozygous transgenic lines of lettuce - Darqui, Flavia Soledad; Radonic, Laura Mabel; Lopez, Nilda Ester; Hopp, Horacio Esteban; Lopez Bilbao, Marisa Gisela (2018)
Background: Lettuce is a globally important leafy vegetable and a model plant for biotechnology due to its adaptability to tissue culture and stable genetic transformation. Lettuce is also crucial for functional genomics research in the Asteraceae which includes species of great agronomical importance. The development of transgenic events implies the production of a large number of shoots that must be differentiated between transgenic and non-transgenic through the activity of the selective agent, being kanamycin the most popular. Results: In this work we adjusted the selection conditions of transgenic seedlings to avoid any escapes, finding that threshold concentration of kanamycin was 75 mg/L. To monitor the selection system, we studied the morphological response of transgenic and non-transgenic seedlings in presence of kanamycin to look for a visual morphological marker. Several traits like shoot length, primary root length, number of leaves, fresh weight, and appearance of the aerial part and development of lateral roots were affected in non-transgenic seedlings after 30 d of culture in selective media. However, only lateral root development showed an early, qualitative and reliable association with nptII presence, as corroborated by PCR detection. Applied in successive transgenic progenies, this method of selection combined with morphological follow-up allowed selecting the homozygous presence of nptII gene in 100% of the analyzed plants from T2 to T5. Conclusions: This protocol allows a simplified scaling-up of the production of multiple homozygous transgenic progeny lines in the early generations avoiding expensive and time-consuming molecular assays.